Manajemen Stres terhadap Kepuasan Kerja Guru dan Manajemen Waktu Pembelajaran Siswa di SDS Islam An Nizam Medan - Rubino, Rubino; Rambe, Ali Akbar; Siregar, Awaluddinsyah (EduInovasi: Journal of Basic Educational Studies, 2024)
This research discusses stress management on teacher job satisfaction and student learning time management at SDS Islam An Nizam Medan. The type of research used is qualitative. Qualitative method produces descriptive data in the form of written or spoken words from people and observed behaviors. By using qualitative data collected directly in the field. The primary data source for this research is teachers and students, while the secondary data source includes profile data, school history, vision and mission, stress management theory on teacher job satisfaction, and student learning time management theory. Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research found that teacher stress management at SDS Islam An Nizam Medan is an effort to deal with stress or pressure in the work environment. The purpose of stress management itself is to improve the quality of teachers' lives so that they are better able to design solutions to problems that arise, especially those related to the causes of stress in the workplace. Student learning time management at SDS Islam An Nizam Medan shows that the students have set goals, arranged schedules, set priorities, been assertive, avoided procrastination, and minimized wasted time.